Comparative transcriptomic analysis of loquat floral fragrance and hormone synthesis regulation across developmental stages in petals and stamens - Huang, Jia-Qi; Wen, Jia-Qi; Wu, Fan; Zhou, Peng; Zhang, Jing-Jing; Wang, Lin-Xuan; Li, Hong-Liang (Frontiers in Plant Science, 2025)
IntroductionLoquat Eriobotrya japonica is a native plant in China that blooms at low temperatures in early winter, and the floral fragrance volatiles from the petals and stamens of loquats’ flowers are attractive to wild pollinators like Chinese honeybees. Thus, it was necessary to reveal the biosynthesis of floral fragrance and hormone regulation involved in the insect pollination of loquats’ flowers.MethodsHere, the volatile contents of petals and stamens were significantly higher than those of other parts of the loquat flower through the analysis of GC, and a key loquat flowers’ compound 4-methoxybenzaldehyde has the highest content among all volatile components. The transcriptomics of six samples of loquat flowers’ petals and stamens at different developmental stages of bud (Bu), exposed (Ex), and bloom (Bl) were obtained.ResultsPCA analysis indicates that petals developed earlier than stamens due to the number of up-regulated petal genes being much higher than that of stamens in the bud stage, and the number of up-regulated stamen genes increasing rapidly at the stages of exposed and bloom. KEGG analysis revealed that petals and stamens DEGs were enriched in two pathways of plant hormone signal transduction and phenylpropanoid biosynthesis. Among them, some key genes related to the synthesis of the fragrance components were screened, and showing a strong positive correlation with phenethyl alcohol and 4-methoxybenzaldehyde. The synthesis of hormones such as gibberellin and growth hormone were also screened. Finally, real-time PCR was used to validate the screening of 12 genes related to floral fragrance and hormone synthesis. Except for ACO (1-Aminocyclopropane-1-carboxylate oxidase), most other genes located in the petals were expressed in significantly higher abundance than in the stamens. Among these, the expression of PAAS (Phenylacetaldehyde synthetase), OMT (O-methyltransferase), GA2OX (Gibberellin 2-β-dioxygenase) were consistent with the development of loquat flower.DiscussionTheir high expression promoted the synthesis and release of floral fragrance and then may effectively attract pollinators. This study enriches the molecular mechanism of the release, synthesis and regulation of loquat floral fragrances and provides a theoretical basis for the co-evolutionary pollination between Chinese honey bees and loquat flowers in early winter.